2020
DOI: 10.1007/s00125-020-05237-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma circulating miR-23~27~24 clusters correlate with the immunometabolic derangement and predict C-peptide loss in children with type 1 diabetes

Abstract: Aims/hypothesis We aimed to analyse the association between plasma circulating microRNAs (miRNAs) and the immunometabolic profile in children with type 1 diabetes and to identify a composite signature of miRNAs/immunometabolic factors able to predict type 1 diabetes progression. Methods Plasma samples were obtained from children at diagnosis of type 1 diabetes (n = 88) and at 12 (n = 32) and 24 (n = 30) months after disease onset and from healthy control children with similar sex and age distribution (n = 47).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 62 publications
2
43
0
Order By: Relevance
“…Based on the high numbers of miRNAs and their involvement in virtually all biological processes, including immune regulation, multiple studies investigated their biomarker potential in the context of islet autoimmunity and T1D (42,56,66,(85)(86)(87)(88)(89)(90)(91). In contrast to the majority of disease symptoms, biomarkers enable the objectively quantifiable characterization of a disease and its progression.…”
Section: Mirnas As Biomarkers For Islet Autoimmunity and T1dmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the high numbers of miRNAs and their involvement in virtually all biological processes, including immune regulation, multiple studies investigated their biomarker potential in the context of islet autoimmunity and T1D (42,56,66,(85)(86)(87)(88)(89)(90)(91). In contrast to the majority of disease symptoms, biomarkers enable the objectively quantifiable characterization of a disease and its progression.…”
Section: Mirnas As Biomarkers For Islet Autoimmunity and T1dmentioning
confidence: 99%
“…Similarly, levels of the miR23~27~24 cluster were increased during disease progression in children with T1D and correlated with osteoprotegerin abundance. Importantly, combining the levels of osteoprotegerin and the miR23~27~24 cluster in plasma of newly diagnosed T1D patients enabled the prediction of insulin secretion 12 months after diagnosis (86).…”
Section: Cell-free Circulating Mirnasmentioning
confidence: 99%
“…In addition, distinct circulating miRNA profiles between subjects with obesity and T2D aroused considerable attention given their potential as biomarkers for these diseases. Indeed, strong correlations were found between some circulating miR-NAs and the development of metabolic syndrome [59], obesity [60,61], diabetes [32,62,63] and/or linked to CVD [37,64]. Nowadays, miRNAs are attractive candidates as innovative biomarkers and have been proposed to promote the progression to diabetes [29,33,62].…”
Section: Mirnas and Cardiovascular Risk Factors (Crfs)mentioning
confidence: 99%
“…Indeed, strong correlations were found between some circulating miR-NAs and the development of metabolic syndrome [59], obesity [60,61], diabetes [32,62,63] and/or linked to CVD [37,64]. Nowadays, miRNAs are attractive candidates as innovative biomarkers and have been proposed to promote the progression to diabetes [29,33,62]. Furthermore, in bariatric metabolic surgery (BMS), miRs might be effective for making the decision about surgery and/or predicting weight loss after BMS [65], providing targets for future treatments.…”
Section: Mirnas and Cardiovascular Risk Factors (Crfs)mentioning
confidence: 99%
“…For example, Dong et al [8] identified miR-182 as a new negative regulator of fat formation and a potential therapeutic target for obesity. In addition, Garavelli et al [9] reported that miR-24-3p is upregulated in the progression of type 1 diabetes. Many investigations reported that obesity is associated with a series of metabolic syndrome, of which diabetes is one of the main complications [10].…”
Section: Introductionmentioning
confidence: 99%